History and prospects of development of the Institute of Agro-Biotechnologies of Komi Science Centre of the Ural Branch of the Russian Academy of Sciences - A. A. Yudin; V. G. Zainullin (Аграрная наука Евро-Северо-Востока, 2021)
Agricultural science in the Komi Republic dates back to 1911, when the Pechora Agricultural Experimental Station was opened on the initiative of the Northern researcher A.V. Zhuravsky. It was the first scientific institution of such specialization in the north of Russia above 65° north latitude. Zhuravsky identified the main tasks facing the agricultural science of the North: the development of agriculture (improvement of soil fertility, development of swamps for agricultural use), meadow and crop production, including vegetable growing, floriculture and fruit growing. He also defined the basis of agricultural production in the North – animal husbandry. While carrying out the studies, A.V. Zhuravsky Institute of AgroBiotechnologies solves all the problems raised. The modern structure of the Institute has three departments: the Department of Agriculture of the Far North, the Department "Pechora Experimental Station" and the Department of Agricultural Genomics organized on the basis of the youth laboratory in 2019. Over the past 20 years, the Institute has produced 12 varieties of perennial grasses, seven of which have been zoned. Among new breeding achievements are Pamyati Zhuravskogo Serpukh crowned (Serratula coronata L.) variety with an increased content of biologically active substances, potato varieties Zyryanets and Vychegodsky for food purpose, resistant to drought, cancer pathogen and golden nematode, highly resistant to late blight. Research on the technology of production of complex forms of nematocidal and insecticidal bio-preparations as a means of protecting agricultural crops from various soil-dwelling phytophages has begun. Thanks to the efforts of the Institute staff, in close cooperation with the farmers of the Arctic region of the Komi Republic, the Pechora sheep breed was preserved, and breeding work with rare native groups was widely developed. The Institute is the only agricultural research institution in the Komi Republic that provides scientific support for Nothern reindeer husbandry.